TETANUS IMMUNIZATION STATUS AND KNOWLEDGE AMONG UNIVERSITY FEMALES AND DOCTORS AT WAD-MEDANI, SUDAN: A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Motassem, Omnia; Abdien, Rehab; Alnour, Alaa; Moawia, Hagir; Abdalla, Doaa; Moawia, Doaa; Yousif, Abrar; Ali, Shorooq; Awad, Essra; Ragb, Marwa; Ais, Maha; Abdelrahim, Musab (Student’s Journal of Health Research Africa, 2024)
Background Tetanus is a bacterial disease with the majority of reported cases being birth-associated due to unhygienic deliveries and lack of routine maternal vaccination, however, it can be prevented by routine vaccination. The current study aimed to determine tetanus vaccination status and knowledge among university females of childbearing age and the doctors who comprise an important category of maternal healthcare service delivery at Wad-Medani City, Sudan, based on the recommended WHO guidelines. Methods A descriptive cross-sectional survey was conducted using two types of researcher-administered questionnaires. Results The majority of the surveyed females were never (41.6%) or didn’t know (22.4%) whether they were vaccinated or not, while some were incompletely vaccinated (26.4%), and few (9.6%) were completely vaccinated with the 5 doses of tetanus vaccine. The main reason for none or incomplete vaccination among the females was the lack of awareness (77.4%). On the other hand, 31% of the respondent doctors knew the correct target population to achieve maternal tetanus elimination as recommended by the documented guidelines with only 25% who knew the complete set of vaccine doses, while 63% were under the misconception that it should target only pregnant women or patients with wounds. Further analysis showed that females who have given birth to children or had a history of pregnancy were more likely to receive the complete 5 doses of the vaccine, while correct knowledge was found higher among doctors with advanced years of experience. Conclusion Tetanus vaccination coverage was relatively poor, and the main reason was the lack of knowledge about the vaccination program and its importance. Recommendation Improving public knowledge through media sources along with other guidance at healthcare facilities can play a vital role in imparting immunization. It is also necessary to ensure the availability of the vaccine and its accessibility for all females.